TRENDS IN THE MODERN APPROACH TO PRESCHOOL EDUCATION: PARADIGMS (Conferencea, 2022)
The article is devoted to substantiation of a new paradigm of preschool education, based on the heuristic possibilities of the concept of functional asymmetry of human brain being a system-forming factor for building a new paradigm of education. It is proved that the development of a personality being a free essence presupposes three stages concerning concrete educational technology: up to 6-7 the socio- pedagogical influence on a child must be paradoxical and ambiguous (the dominance of right hemisphere); from 7 to 14 the socio-pedagogical influence on young people must be strict and " one-dimensional " (the dominance of left hemisphere); after 14 the socio-pedagogical influence on young people must be "one¬dimensional" and "multidimensional" simultaneously (the state of hemispheric harmony): as electroencephalographic research shows the hemispheric functional harmony is revealed in the state of meditation and creativity being the major purpose of man's development.